Exploration of the relationship between GRAIL and Cbl-b - Winograd, Paul (My University, 2010)
The E3 ligases GRAIL and Cbl-b are necessary for the induction of CD4+ T cell anergy. Using CD4+ T cells from wildtype (WT) and Cbl-b knockout (Cbl-B -/-) mice, we investigated the relationship between GRAIL and Cbl-b. Induction of anergy led to an 8-fold increase in GRAIL mRNA expression in WT T cells compared to the Cbl-b -/- T cells. In contrast, ectopic expression of GRAIL in WT and Cbl-b -/- CD4+ T cells led to a 305 decrease in proliferation in both groups relative to their respective GFP-transduced control, providing evidence that GRAIL functions independently of Cbl-b for conveyance of an anergic phenotype. In sum, these data suggest a Cbl-b dependent role for optimal upregulation of GRAIL and mRNA under anergizing conditions and a Cbl-b independent functional role for GRAIL in the anergic phenotype.
Abstract: 2 p. Complete paper: 20 p.
Keywords: Pediatrics; Biochemistry